Tecno-morfología como estrategia de diseño - Reissig, Pedro (2012)
Techno-morphology explores the form / structure relationship, interested in resistance by form rather than matter. This paradigm is known as Lightweight Structures when it is done on an architectural scale and has been installed in general culture as a new genre over the last 50 years. Far from being mechanistic or high-tech, this approach is based on nature's own structures as a design strategy, celebrating its functionality, efficiency and beauty. The Thesis examines the essence of this paradigm for greater understanding and to open it up to new possibilities, moving away from formal and generic trends. There are four factors that influence the design of every human product at any scale and dimension; form (understood as different morphological possibilities), matter (inputs, ingredients), technology (processes for transformation of materials) and structure (the organization of the form so that it is functional). The particular relationship between these four variables defines the identity and success of design. This thesis includes four case studies (Tensegrity, Catenary, Fluid Origami, Woven) proposed by the author, each one forms an Atlas that includes applied examples, glossary, typological maps and new proposals to explore.